GAMBARAN PENGETAHUAN IBU TENTANG ASI EKSKLUSIF PADA BAYI USIA 0-6 BULAN DI KECAMATAN RAMBIPUJI KABUPATEN JEMBER - Susanto, Tantut; Onim, George; Rasni, Hanny; Fauziah, Wahyuni (JURNAL SVASTA HARENA RAFFLESIA, 2024)
Background: Coverage of exclusive breastfeeding in infants aged 0-6 months in Indonesia in 2016 is still low at 29.5%. Based on the WHO report (2018), there are 50% of mothers who breastfeed their babies with exclusive breastfeeding. Based on data from 2017 it was found that there were 84.06% of mothers giving exclusive breastfeeding to their babies. Based on data from East Java Province in 2017, 75.7% of mothers gave exclusive breastfeeding to their babies. Objective: The purpose of this study is to illustrate the knowledge of mothers about exclusive breastfeeding in infants aged 0-6 months in Rambipuji District, Jember Regency. Method:This study also uses a descriptive study using a cross-sectional approach that is only done once at a time. The research subjects that will be observed once in this study are the factors that influence exclusive breastfeeding by mothers who have babies aged 0-6 months in Rambipuji District, Jember Regency. Results: it is known that a high proportion of knowledge is 69 (68.3%), followed by a moderate level of knowledge which is 32 (31.7%), and no mothers with low knowledge about exclusive breastfeeding are found. Mother's knowledge about Exclusive ASI has three levels of assessment, namely low (score ≤4), moderate (score 4-7), and high (score> 7). 10 items of mother's knowledge questions about Exclusive ASI varied in value (p <0.001). Conclusion: Based on the characteristics of the respondents in this study were mothers with children aged 0-6 months. The results showed 68% of respondents exclusively breastfed their babies. Respondents based on breastfeeding experience who exclusively breastfeed evenly distribute.